2021
DOI: 10.5296/jas.v9i3.18476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Invasive Aquatic Plants (Azolla a., Myriophyllum a. and Cyperus a.) Biochar Amendment on Maize Growth: An Assessment

Abstract: The management of invasive aquatic plants (IAPs), which is primarily accomplished through manual grubbing, incurs significant costs for populations, especially since the operations must be renewed on a regular basis. Converting IAPs into biochar for use as soil amendment will help offset the costs of this mechanical control strategy, while also improving carbon sequestration, soil fertility and crop yields. The objective of this study is to examine the effects of using IAPs biochar amendment on the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Azolla is harvested in large quantities and fed to cattle and pigs as feed (Tarrif et al, 2021). It was also demonstrated that feeding Azolla to broilers produced growth and body weight values comparable to corn-soybean meal (Ouedraogo et al, 2021). Digested Azolla manure left over from biogas production was suitable as fish pond fertiliser and in a study of lactating cows (Abdelatty et al, 2021), it was discovered that Azolla could be used as a feed ingredient, with milk yield and fat percentage remaining at the same levels as when fed conventional feed.…”
Section: Azolla As a Livestock Nutritional Supplementmentioning
confidence: 94%
See 1 more Smart Citation
“…Azolla is harvested in large quantities and fed to cattle and pigs as feed (Tarrif et al, 2021). It was also demonstrated that feeding Azolla to broilers produced growth and body weight values comparable to corn-soybean meal (Ouedraogo et al, 2021). Digested Azolla manure left over from biogas production was suitable as fish pond fertiliser and in a study of lactating cows (Abdelatty et al, 2021), it was discovered that Azolla could be used as a feed ingredient, with milk yield and fat percentage remaining at the same levels as when fed conventional feed.…”
Section: Azolla As a Livestock Nutritional Supplementmentioning
confidence: 94%
“…Weed growth is stifled when Azolla forms a thick, almost opaque mat. There are most likely two mechanisms at work here, the most efficient of which is light deprivation for immature weed seedlings due to sunlight obstruction (Ouedraogo et al, 2021). The other is a dense, interlocking Azella mat that provides physical resistance to the emergence of weed seedlings (Marzvan et al, 2021).…”
Section: Controlling the Spread Of Aquatic Weedsmentioning
confidence: 99%